"Goa Raksasa" di Desa Giri Emas dan Potensinya Sebagai Sumber Belajar Sejarah di SMA - Sutiarsana, Putu Rian; I Made Pageh; Desak Made Oka Purnawati (Widya Winayata : Jurnal Pendidikan Sejarah, 2025)
The “Goa Raksasa or Giant Cave” site is in Giri Emas Village, Sawan Subdistrict, Buleleng Regency, Bali. The cave resembles a water tunnel and is considered mystical by the local community. It is also associated with the traditional irrigation system, subak, and the Tri Hita Karana (THK) philosophy. This research aims to explore the local naming of the “Goa Raksasa or Giant Cave” in Giri Emas Village, examine the evidence that may explain the origins and functions of the “Goa Raksasa or Giant Cave,” and analyze the aspects of the site that hold potential as a source for historical learning. This study is qualitative and employs historical research methods through several stages: heuristic (gathering historical sources) using observation, interviews, and document study; source criticism to determine the authenticity and credibility of historical sources through both external and internal critique; interpretation of the sources; and historiography, or the writing of history, based on diachronic and synchronic thinking principles guided by the 5W+1H approach, supported by auxiliary sciences such as archaeology and various social-science-based interdisciplinary approaches (eclectic method). The findings indicate that the designation “Giant Cave” is rooted in the history of the Ancient Balinese period, during which the cave was believed to have been constructed in Saka year 933 or 1011 AD, under the reign of King Anak Wungsu. The site’s narrative later evolved into a myth about a giant who abducted a Rejang dancer during the Revolutionary era. The supporting evidence includes the cave’s interior features, surrounding plantations, a small traditional water channel near the cave, the cave’s proximity to a water source, and the beliefs of the residents of Giri Emas Village and its surroundings. Additional interpretations from various sources also support these findings. Aspects of the “Giant Cave” that show potential as a source of historical learning at the senior high school level include its knowledge dimension, spiritual values, social context, archaeological remains, and historical significance. These components have been compiled into a Teaching Module to be utilized as an educational resource for history learning in high schools.